Cooperative Learning Model to Improve Student Learning Outcomes in Islamic Education Learning at SD Negeri 3 Lembah Sabil - Purdi Abbas (MANDAILING GLOBAL EDUKASIA, 2025)
Islamic religious education is a crucial subject in formal education, especially general education. This is because Islamic religious education is the sole vehicle for imparting religious knowledge in the formation of students' morals, therefore, Islamic religious learning plays a crucial role. It is important to note that further efforts are needed to help students understand the teaching of Q.S. Al-Hujurat verse 13. One model that can be used is Cooperative Learning. The use of the Cooperative Learning Model in the learning process of Q.S. Al-Hujurat verse 13 is expected to improve student learning outcomes, as expected. Based on the researcher's experience teaching in the classroom using conventional methods, the researcher found that student enthusiasm, motivation, and learning outcomes were low. This is because during teaching, the teacher is the sole source of knowledge and the center of learning. Therefore, the researcher conducted a study aimed at improving the learning outcomes of fourth-grade students in Islamic Religious Education learning on Q.S. Al-Hujurat verse 13 with cooperative learning method in grade 4 of SD Negeri 3 Lembah Sabil, Aceh Barat Daya Regency, academic year 2024-2025. The subjects of this study were grade 4 students of SD Negeri 3 Lembah Sabil in the field of Islamic Religious Education with the subject matter of Q.S. Al-Hujurat verse 13. This study uses a quantitative approach with the type of classroom action research. The data collected in this study through pre-cycle tests, final tests of each cycle, observations, and interviews. The Cooperative Learning method can improve student learning outcomes on the material I Am a Pious Child of Islamic Religious Education subject for grade 4 of SD Negeri 3 Lembah Sabil, as many as 88% of students or as many as 9 students completed the learning with an average grade of 80.62. This means that the use of the cooperative learning method is quite effective in improving the learning outcomes of grade IV students in Islamic Religious Education learning on Q.S. Al-Hujurat verse 13 material at SD Negeri 3 Lembah Sabil.